Electrochemical sensor for capsaicinoids based on Ni-reinforced CNTs / sulfonated rGO composites

The construction of electrochemical sensors through Ni-enhanced CNTs/sulfonylated rGO composites solves the problems of low detection sensitivity and poor selectivity of capsaicin substances in the prior art, and achieves high sensitivity, rapid and economical detection effects.

CN116514116BActive Publication Date: 2025-02-07ANHUI THREE SQUIRRELS ELECTRONICS BUSINESS +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310516053.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-09
Publication Date
2025-02-07
Estimated Expiration
2043-05-09

AI Technical Summary

Technical Problem

In the detection of capsaicin substances, the existing technology has problems such as complex operation, high cost, low sensitivity of rapid detection methods, poor selectivity and high variability of results in capsaicin substance detection.

Method used

Electrochemical sensors were constructed using Ni-enhanced CNTs/sulfonated rGO composite material, Ni-CNTs and S-rGO were prepared by the enhancement and sulfonated functional group regulation strategies of nickel atoms, and the two were combined by ultrasound to form a composite material for detection Capsaicin substances.

Benefits of technology

It has achieved a low detection limit and a wide detection range for capsaicin substances, high sensitivity, fast and economical detection effects, and has good anti-interference, stability and accuracy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116514116B_ABST
    Figure CN116514116B_ABST
Patent Text Reader

Abstract

The invention discloses an electrochemical sensor for capsaicinoids constructed by using a Ni-enhanced CNTs / sulfonated rGO composite material. Ni-CNTs and S-rGO are prepared respectively by nickel atom doping and sulfonated functional group regulation strategy, and the two are combined by ultrasound to obtain a composite material. A water-dispersed droplet containing the composite material of the invention is applied to a clean glassy carbon electrode surface, and then dried to obtain an electrochemical sensor for detecting capsaicinoids. The electrochemical sensor has good anti-interference, stability and accuracy, realizes ultra-sensitive detection of capsaicinoids, and has great potential for application in casual marinated meat.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanomaterials and food detection, and particularly relates to an electrochemical sensor for capsaicinoids constructed using a Ni-enhanced CNTs / sulfonated rGO composite material. Background Art

[0002] Capsaicinoids are the main contributors to spiciness, and the main components of this type of substance are capsaicin and dihydrocapsaicin, which account for more than 90% of the total capsaicinoids. Casual marinated meat products are very popular products in the casual food market, with huge market development space, but the spicy labeling of casual marinated meat products is confusing and the description method is subjective, which has caused various commercial disputes. Determining the content of capsaicinoids in casual marinated meat products and establishing a scientific and objective numerical evaluation method for spiciness is an important way to solve this bottleneck problem. However, there are still some problems with the current conventional capsaicinoid detection methods, including the complex operation and high cost of large instruments; the existing rapid detection methods have low sensitivity, poor selectivity and large variability in results.

[0003] The detection technology based on electrochemical sensors of carbon-based materials has gradually emerged in the field of capsaicinoid detection in recent years due to its advantages such as low price, simple operation, fast detection speed, portability, high sensitivity and relative stability, and has become a "promising alternative method". Carbon-based materials are the core of electrochemical sensors for capsaicinoids, but the poor dispersibility of carbon-based materials and the insufficient electrocatalytic performance for capsaicinoids limit their further application. Therefore, the preparation of excellent electrochemical sensors that can be used for the detection of capsaicinoid content is the key to solving the above problems. Summary of the invention

[0004] One of the purposes of the present invention is to provide a Ni-enhanced CNTs / sulfonated rGO composite material and a preparation method thereof. Nickel is an efficient conductor with low overpotential, and has the advantages of large surface area and high conductivity. In addition, the cost of nickel is much lower than that of precious metals such as gold and platinum. Nickel-enhanced carbon nanotubes (CNTs) have higher conductivity and catalytic activity than single CNTs. Nickel nanoparticles have a certain enhancement effect on the electrocatalysis of capsaicin by carbon nanotubes. Compared with single graphene, sulfonated graphene has higher proton conductivity, water absorption, mechanical properties and electrochemical properties. At the same time, the sulfonated graphene has the dual advantages of oxidized graphene and reduced oxidized graphene. It is highly hydrophilic while maintaining the high conductivity and high catalytic performance of graphene, so that the graphene is more evenly dispersed in water, and a stronger catalytic effect of capsaicin can be exerted. The present invention prepares Ni-CNTs and S-rGO respectively through the enhancement of nickel atoms and the regulation strategy of sulfonated functional groups, and combines the two by ultrasound to obtain a composite material, which can be applied to electrochemical sensors for detecting capsaicinoids and has a low detection limit and a wide detection range.

[0005] The second object of the present invention is to provide an electrochemical sensor for detecting capsaicinoids and a preparation method thereof, which is obtained by applying water-dispersed droplets containing the Ni-enhanced CNTs / sulfonated rGO composite material described in the present invention on the surface of a clean glassy carbon electrode and drying it; this electrochemical sensor is used to achieve highly sensitive, rapid and economical detection of capsaicinoids.

[0006] The third object of the present invention is to provide a method for detecting the content of capsaicinoids. Using the electrochemical sensor described in the present invention as a working electrode, the detection range of capsaicinoids is 0.01-100.00 μmol / L, the detection limit is as low as 1 nmol / L, and it has good anti-interference, stability and accuracy, achieving ultra-sensitive detection of capsaicinoids, and has great potential for application in casual marinated meat.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing a Ni-enhanced CNTs / sulfonated rGO composite material, the preparation method comprising the following steps:

[0009] (1) dispersing graphene oxide in ultrapure water, adding phenylhydrazine-4-sulfonic acid hemihydrate (4-HBS) thereto and stirring and mixing evenly, then transferring to a reactor, hydrothermally reacting at 120-150° C. for 4-8 hours, washing and drying to obtain a sulfonated rGO material;

[0010] (2) Ni-enhanced CNTs material and sulfonated rGO material are dispersed in ultrapure water and subjected to ultrasonic reaction to obtain Ni-enhanced CNTs / sulfonated rGO composite material (Ni-CNTs / S-rGO).

[0011] In step (1), the mass ratio of graphene oxide to 4-HBS is 15 to 25:1.

[0012] In step (2), the mass ratio of Ni-enhanced CNTs material to sulfonated rGO material is 1:1.5-3; and the ultrasonic reaction time is 1.5-3h.

[0013] In step (2), the preparation method of Ni-enhanced CNTs material (Ni-CNTs) is as follows: prepare a mixed aqueous solution containing CNTs, Ni2SO4.6H2O, NiCl2.6H2O and H3BO3, add the mixed aqueous solution into a high-temperature reactor, and perform hydrothermal reaction at 160-200°C for 8-12h. After centrifugation, washing and drying, Ni-enhanced CNTs material can be obtained.

[0014] In the mixed aqueous solution, the concentration ratio of CNTs, Ni2SO4.6H2O, NiCl2.6H2O and H3BO3 is 1-5 mg / mL: 0.2-1.0M: 0.05-0.3M: 0.1-1.0M.

[0015] The present invention also provides a Ni-enhanced CNTs / sulfonated rGO composite material prepared by the preparation method, in which tubular Ni-enhanced CNTs cover the surface of layered sulfonated rGO, and sulfonated rGO sheets enhanced by Ni-CNTs are alternately stacked to form a three-dimensional structure.

[0016] The present invention also provides an electrochemical sensor for detecting capsaicin, comprising an electrode and a composite material loaded on the electrode; the composite material is the Ni enhanced CNTs / sulfonated rGO composite material described in the present invention.

[0017] The present invention also provides a method for preparing an electrochemical sensor for detecting capsaicin, wherein water-dispersed droplets containing Ni-enhanced CNTs / sulfonated rGO composite materials are applied to the surface of a clean glassy carbon electrode, and the electrochemical sensor for detecting capsaicin is obtained after drying.

[0018] The present invention also provides application of the electrochemical sensor for detecting capsaicin in detecting the content of capsaicin.

[0019] The present invention also provides a method for detecting the content of capsaicinoids, the method comprising the following steps:

[0020] 1) Dissolve equal volumes of capsaicin standard solutions or dihydrocapsaicin standard solutions with different concentration gradients in an electrolyte solution;

[0021] 2) using the electrochemical sensor of the present invention as a working electrode, and forming a three-electrode system with an auxiliary electrode and a reference electrode to detect the electrochemical signals of each sample in step 1);

[0022] 3) constructing a standard curve with the response value of the electrochemical signal as the ordinate and the concentration of the capsaicin standard solution or the dihydrocapsaicin standard solution as the abscissa, and obtaining a linear equation;

[0023] 4) extracting capsaicin or dihydrocapsaicin from the sample to be tested and dissolving it in an electrolyte solution, repeating the above step 2), and substituting the response value of the electrochemical signal obtained into the linear equation obtained in step 3),

[0024] The content of capsaicinoids can be calculated.

[0025] The electrolyte solution is a hydrochloric acid aqueous solution; the auxiliary electrode and the reference electrode are a platinum electrode and a saturated calomel electrode respectively.

[0026] In step 2), differential pulse voltammetry or cyclic voltammetry can be used for detection.

[0027] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:

[0028] In the preparation method of the Ni-enhanced CNTs / sulfonated rGO composite material provided by the present invention, Ni-CNTs and S-rGO are respectively prepared by nickel atom doping and sulfonated functional group regulation strategy, and the two are combined by ultrasound to obtain a composite material. In the composite material, the introduction of Ni improves the electron transfer rate of c-CNTs, and the design of the sulfonated functional group enables the S-rGO material to have excellent water dispersibility, long-term stability and satisfactory electron transfer ability and catalytic performance.

[0029] After the Ni-enhanced CNTs / sulfonated rGO composite material provided by the present invention is prepared into an electrochemical sensor for detecting capsaicin, the Ni-CNTs / S-rGO assembles to form a three-dimensional stacking structure and interpenetration, thereby increasing the electrochemically active surface area of ​​the modified electrode and exposing more catalytic sites of capsaicinoids. At the same time, the O atoms in the Ni-CNTs / S-rGO capture the electrons on the N atoms, which will cause the electron cloud density of the N atoms to decrease and the electron cloud density of the O atoms to increase, so that a built-in electric field is formed inside the Ni-CNTs / S-rGO, which is conducive to the improvement of the charge transfer rate of the composite material.

[0030] The electrochemical sensor for detecting capsaicinoids provided by the present invention has a detection range of 0.01 to 100.00 μmol / L for capsaicinoids, a detection limit as low as 1 nmol / L, and good anti-interference, stability and accuracy, thereby achieving ultra-sensitive detection of capsaicinoids and having great potential for application in casual marinated meats. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Schematic diagram of the preparation process of Ni-CNTs / S-rGO composite material;

[0032] Figure 2 Microscopic morphology images of different materials, where a is the SEM image of GO, b is the SEM image of S-rGO, c is the SEM image of c-CNTs, d is the SEM image of Ni-CNTs, e and f are SEM images of Ni-CNTs / S-rGO, g and h are TEM images of Ni-CNTs / S-rGO, and i is the EDS image of Ni-CNTs / S-rGO;

[0033] Figure 3 XRD patterns of GO, S-rGO, c-CNTs, Ni-CNTs, and Ni-CNTs / S-rGO;

[0034] Figure 4 FTIR images of GO, S-rGO, c-CNTs, Ni-CNTs, and Ni-CNTs / S-rGO;

[0035] Figure 5 XPS graphs of GO, S-rGO, c-CNTs, Ni-CNTs, and Ni-CNTs / S-rGO;

[0036] Figure 6 For GO / GCE, CNTs / GCE, Ni-CNTs / GCE, S-rGO / GCE, Ni-CNTs / S-rGO / GCE electrodes on [Fe(CN)6] 3- / 4- CV curve diagram in;

[0037] Figure 7 CV curves of capsaicin on GO / GCE, CNTs / GCE, Ni-CNTs / GCE, S-rGO / GCE, Ni-CNTs / S-rGO / GCE electrodes (a) and CV curves of capsaicin at different scan rates when using Ni-CNTs / S-rGO / GCE electrode (b);

[0038] Figure 8 CV curves of the same content of capsaicin and dihydrocapsaicin when using Ni-CNTs / S-rGO / GCE electrode;

[0039] Fig. 9 The effects of deposition potential (a), deposition time (b) and electrolyte pH on the peak current of capsaicin using Ni-CNTs / S-rGO / GCE electrode.

[0040] Fig.10 Standard curve for detecting capsaicin in Ni-CNTs / S-rGO / GCE;

[0041] Fig.11 This is the stability test of Ni-CNTs / S-rGO / GCE for detecting capsaicin, where a is the stability between different electrodes and b is the storage stability of the electrode;

[0042] Fig.12 Anti-interference test of Ni-CNTs / S-rGO / GCE for detecting capsaicin. DETAILED DESCRIPTION

[0043] The present invention is described in detail below with reference to the embodiments.

[0044] The GO used in the present invention was purchased from Suzhou Carbon Graphene Technology Co., Ltd.; 4-HBS was purchased from Sigma-Aldrich.

[0045] The preparation method of Ni-enhanced CNTs material (Ni-CNTs) is as follows: prepare a mixed solution containing 3 mg / mL CNTs, 0.5MNi2SO4.6H2O, 0.15M NiCl2.6H2O and 0.5M H3BO3, ultrasonically mix at 300w and 40kHz, and then magnetically stir at 75°C for 8 hours. Next, add the mixed solution into a high-temperature reactor and react at 180°C for 10 hours. Finally, centrifuge the mixture and wash it alternately with deionized water and anhydrous ethanol for 3 times, and vacuum dry it at 60°C for 12 hours to obtain the product.

[0046] Example 1

[0047] A method for preparing a Ni-enhanced CNTs / sulfonated rGO composite material (Ni-CNTs / S-rGO) comprises the following steps:

[0048] (1) 35 g of GO was added to ultrapure water at a concentration of 2 mg / mL for ultrasonic dispersion. Subsequently, 1.8 g of 4-HBS was added to the GO dispersion under magnetic stirring conditions and stirred for 10 min to fully mix the system to obtain a mixture. The mixture was sealed in a 100 mL polytetrafluoroethylene autoclave and maintained at 140°C for 6 h. The cooled reactants were washed alternately with ultrapure water and anhydrous ethanol for 3 times, and finally dried in a vacuum drying oven at 60°C for 12 h to obtain S-rGO.

[0049] (2) 10 mg of Ni-CNTs and 20 mg of S-rGO were added to 30 mL of ultrapure water and ultrasonicated for 2 h to obtain a Ni-CNTs / S-rGO dispersion. The Ni-CNTs / S-rGO dispersion was filtered, washed three times with ultrapure water, and dried to obtain a Ni-CNTs / S-rGO composite material.

[0050] SEM of GO, S-rGO, c-CNTs, Ni-CNTs, Ni-CNTs / S-rGO, TEM of Ni-CNTs / S-rGO, EDS of Ni-CNTs / S-rGO Figure 2 As shown. Figure 2 As can be seen from Figures 2a and 2b, there is almost no difference in the morphology between GO and S-rGO, and it can be observed that both of them present a typical wrinkled layered structure. Figure 2 As can be seen from Figures c and 2d, CNTs and Ni-CNTs were observed to present intertwined tubular structures, but the surface of Ni-CNTs was obviously covered with many small particles that were aggregated into clusters. This was the result of electroplating nickel nanoparticles on the surface of CNTs. Figure 2 As can be seen from e and 2f, Ni-CNTs / S-rGO is a layered S-rGO surface loaded with a large number of tubular Ni-CNTs, and the S-rGO sheets reinforced by Ni-CNTs are alternately stacked to form a three-dimensional structure. The staggered Ni-CNTs and S-rGO materials form a Ni-CNTs / S-rGO composite. Figure 2 In the TEM images of Ni-CNTs / S-rGO in e and 2f, it can be more intuitively observed that Ni-CNTs cover the surface of S-rGO, which also confirms the results of SEM.

[0051] The crystal structure changes during the preparation process of Ni-CNTs / S-rGO were studied by XRD. The XRD patterns of GO, S-rGO, c-CNTs, Ni-CNTs, and Ni-CNTs / S-rGO are shown in the figure below. Figure 3As shown. GO shows a strong diffraction peak at 12.3°, which corresponds to the (002) plane of graphite and is mainly attributed to graphite oxidation. When GO is reduced to S-rGO, the peak at 12.3° completely disappears, but diffraction peaks corresponding to the rGO (002) and (100) crystal planes appear near 25.2° and 43.6°, respectively, indicating that GO is successfully reduced. In c-CNTs, the diffraction peaks at 25.9° and 43.5° correspond to the (022) and (002) crystal planes of CNTs, respectively, which is a very typical CNTs spectrum. When metal Ni is coated on c-CNTs, part of the crystal structure of CNTs is retained in Ni-CNTs, and new diffraction peaks appear at 39.1°, 43.0°, 44.5°, 58.5°, 71.2° and 77.9°, which are respectively attributed to the crystal planes (010), (002), (011), (012), (110) and (103) of Ni. As for Ni-CNTs / S-rGO, its XRD spectrum contains diffraction peaks of both S-rGO and Ni-CNTs, but the intensity is reduced, which may be due to the mutual insertion of S-rGO and Ni-CNTs under the action of ultrasound, which destroys part of the crystal structure of their respective materials. Compared with Ni-CNTs and S-rGO, the diffraction peak position of Ni-CNTs / S-rGO moves slightly, which can be attributed to the relaxation effect and crystal strain generated during the composite process of the two materials.

[0052] FTIR images of GO, S-rGO, c-CNTs, Ni-CNTs, and Ni-CNTs / S-rGO are shown in Figure 2. Figure 4 As shown, the bands at 3440 cm-1 for all materials are attributed to the stretching vibration of adsorbed water molecules OH, while the bands near 2900 cm-1 in CNTs, Ni-CNTs and Ni-CNTs / S-rGO are attributed to the vibration of -CH2. In the spectrum of GO, the bands in the range of 1040-1720 cm-1 represent CO, COC, C-OH, C=C and C=O in order from low to high wavelength. The bands in S-rGO are highly similar to those of GO, but the intensity decreases, which may be due to the reduction in the proportion of oxygen-containing functional groups during the reduction process. In addition, new bands appeared in S-rGO at 1080 cm-1 and 1120 cm-1, which are attributed to -SO3 provided by 4-HBS. 2- There are also C=C (1590cm-1) and oxygen-containing groups in CNTs, while the spectrum of Ni-CNTs is similar to that of CNTs. As for Ni-CNTs / S-rGO, it also shows -SO3 of S-rGO at 1070cm-1 and 1125cm-1. 2-The wavelengths of the characteristic signal bands in Ni-CNTs / S-rGO have shifted, which may be due to the interaction between the oxygen-containing functional groups in Ni-CNTs and S-rGO.

[0053] XPS images of GO, S-rGO, c-CNTs, Ni-CNTs, and Ni-CNTs / S-rGO are shown in Figure 2. Figure 5 As shown in the figure, all materials contain C, O and a small amount of N. In addition, S-rGO contains S, Ni-CNTs contains Ni, and Ni-CNTs / S-rGO composites contain C, N, O, S and Ni at the same time, which is consistent with the results of EDS. Figure 5 As can be seen in b), S-rGO has a new response peak at 285.2eV relative to GO, which represents the formation of CS bonds, indicating that 4-HBS as a reducing agent and modifier has been grafted onto GO. The CS bonds in Ni-CNTs / S-rGO also come from S-rGO. In the N1s high-resolution spectrum ( Figure 5 c) shows that all five materials can deconvolute three response peaks, which represent pyridinic nitrogen (C≡N, -NH2), pyrrolic nitrogen (NH, N=N) and graphitic nitrogen from low to high binding energy. The formation of pyridinic, pyrrolic and graphitic nitrogen can significantly improve the conductivity of the composite material and can also serve as active sites for electrochemical reactions. Figure 5 d), all five materials were deconvoluted into three peaks. According to the binding energy from low to high, they are C=O and C-OH bonds. These abundant oxygen-containing functional groups have good electrocatalytic ability, which is conducive to the adsorption and electrocatalytic process of capsaicinoids by the modified electrode. Figure 5 In e), the peaks at 857 eV and 874 eV in Ni-CNTs and Ni-CNTs / S-rGO represent Ni 2p 3 / 2 and Ni 2p 1 / 2 , while the peaks near 861eV and 880eV correspond to Ni 2p 3 / 2 and Ni2p 1 / 2 Satellite peaks. In the high-resolution spectrum of S 2p ( Figure 5 f), the peaks in the range of 162.0 eV to 166.5 eV and 166.6 eV to 171.2 eV in S-rGO and Ni-CNTs / S-rGO are respectively caused by S2p from sulfonate groups. 3 / 2 and S 2p 1 / 2Composition of spin split components. Combining the N1s and O1s energy spectra, it is found that compared with Ni-CNTs and S-rGO, all N1s peaks in Ni-CNTs / S-rGO move toward the direction of high binding energy, while all O1s peaks move toward the direction of low binding energy. This may be because in the process of Ni-CNTs / S-rGO binding, the electronegativity of O atoms is higher, thus taking away electrons from N atoms, which will cause the electron cloud density of N atoms to decrease and the electron cloud density of O atoms to increase, thereby promoting charge transfer in Ni-CNTs / S-rGO to form a built-in electric field.

[0054] Example 2

[0055] A method for preparing an electrochemical sensor for detecting capsaicinoids comprises the following steps: applying 1.7 μL of the Ni-CNTs / S-rGO dispersion droplet in step (2) of Example 1 on the surface of a clean glassy carbon electrode, and after drying, obtaining an electrochemical sensor Ni-CNTs / S-rGO / GCE for detecting capsaicinoids.

[0056] Following the same method, 2 μL of 1 mg / mL GO aqueous dispersion, CNTs aqueous dispersion, Ni-CNTs aqueous dispersion, and S-rGO aqueous dispersion were respectively added onto the clean glassy carbon electrode surface. After drying, GO / GCE, CNTs / GCE, Ni-CNTs / GCE, and S-rGO / GCE were obtained, respectively.

[0057] By analyzing the different electrodes at 5mM Fe[(CN)6] 3- / 4- The CV (cyclic voltammetry) curves in the experiment were used to investigate the electron transfer rates of different electrodes. The CV experimental method was as follows: First, the CV mode was selected on the electrochemical workstation CHI660D, with a platinum electrode as the auxiliary electrode, a saturated calomel electrode as the reference electrode, and 5 mM Fe[(CN)6] 3- / 4- The electrolyte was set at a potential range of -0.2 to 0.6 V, a scan rate of 0.1 V / s, and a balance time of 2 s. Then, the prepared different electrodes GO / GCE, CNTs / GCE, Ni-CNTs / GCE, and S-rGO / GCE were inserted into Fe[(CN)6] 3- / 4- The solution was scanned until the curve stabilized.

[0058] like Figure 6As shown in the figure, it can be seen that the peak current value of GO / GCE is significantly lower than that of GCE and is the smallest, that is, the electron transfer rate is the lowest. This is because even though GO has rich functional groups, high hydrophilicity and long-term stability, it still has electronic insulation properties and cannot be directly used as an electrochemical detection material. When GO is reduced by 4-HBS, S-rGO / GCE shows a peak current significantly higher than that of GCE, which shows that S-rGO has excellent conductivity and electron transfer rate. Both CNTs / GCE and Ni-CNTs / GCE have a peak current significantly higher than that of GCE, especially Ni-CNTs has a higher peak current value, which is due to the high conductivity inherent in CNTs carbon nanomaterials, and nickel is a conductor with low overpotential. Ni-CNTs / S-rGO / GCE shows the highest peak current, which indicates that it has the strongest electron transfer rate and the highest conductivity. This phenomenon may come from the synergistic enhancement effect produced by the interaction between Ni-CNTs and S-rGO. According to the Randles-Sevcik equation, the electrochemically active surface areas of the six electrodes are calculated to be GCE0.049cm 2 , GO / GCE 0.031cm 2 、CNTs / GCE 0.064cm 2 、S-rGO / GCE 0.064cm 2 、Ni-CNTs / GCE 0.069cm 2 and Ni-CNTs / S-rGO / GCE 0.079cm 2 .

[0059] GO / GCE, CNTs / GCE, Ni-CNTs / GCE, S-rGO / GCE, Ni-CNTs / S-rGO / GCE were used as working electrodes, platinum electrode was used as auxiliary electrode, saturated calomel electrode was used as reference electrode, pH 1, 50 μM capsaicin hydrochloric acid solution was used as electrolyte, the potential range was set to -0.2-0.6 V, the scan rate was 0.1 V / s, and the equilibrium time was 2 s. The CV responses of GO / GCE, CNTs / GCE, Ni-CNTs / GCE, S-rGO / GCE, and Ni-CNTs / S-rGO / GCE electrodes in capsaicin solution are shown in Figure 2. Figure 7As shown in a, the electrochemical response of capsaicin on GCE and GO / GCE is very weak, which indicates that the weak conductivity and electron transfer rate of GO and GC limit their catalytic ability. In contrast, capsaicin has a clear redox peak on S-rGO / GCE. This is because the GO reduced by 4-HBS is re-endowed with excellent conductivity and electron transfer rate, which not only obtains good dispersibility and high stability, but also gives full play to the catalytic properties of rGO's own functional groups and 4-HBS. At the same time, capsaicin also shows obvious response current on CNTs / GCE and Ni-CNTs / GCE, especially Ni-coated CNTs has better catalytic effect. This may be due to the introduction of Ni, which makes Ni-CNTs have the material advantages of both CNTs and Ni, and plays a certain synergistic catalytic role. Ni-CNTs / S-rGO / GCE has the largest response current to capsaicin. On the one hand, the effective insertion of Ni-CNTs between S-rGO sheets forms a three-dimensional nanostructure, which increases the electrochemical active surface area and electron transfer rate of the composite material. On the other hand, during the composite process of S-rGO and Ni-CNTs, various functional groups and chemical bonds interacted with each other, which may have led to an obvious synergistic effect of Ni-CNTs / S-rGO in the electrocatalysis of capsaicin.

[0060] Ni-CNTs / S-rGO / GCE was used as the working electrode, platinum electrode as the auxiliary electrode, saturated calomel electrode as the reference electrode, and hydrochloric acid solution of capsaicin with a pH of 1 and a concentration of 50 μM as the electrolyte. The potential range was set to -0.2 to 0.6 V, the equilibrium time was 2 s, and the scan rate was changed in the range of 0.03 V / s to 0.2 V / s to test the CV curves of capsaicin at different scan rates. Figure 7 As shown in (b), with the increase of scanning rate, the oxidation peak shifts positively and the reduction peak shifts negatively, and the square root of the scanning rate has a good positive correlation with the peak current, which indicates that the redox process of capsaicin is diffusion controlled.

[0061] Ni-CNTs / S-rGO / GCE was used as the working electrode, platinum electrode as the auxiliary electrode, saturated calomel electrode as the reference electrode, pH 1 and 50 μM capsaicin hydrochloric acid solution, pH 1 and 50 μM dihydrocapsaicin hydrochloric acid solution as the electrolyte, the potential range was set to -0.2-0.6 V, the scan rate was 0.1 V / s, and the equilibrium time was 2 s to test the CV curves of capsaicin and dihydrocapsaicin. Figure 8 As shown, it is proved that capsaicin and dihydrocapsaicin still have the same electrochemical behavior on Ni-CNTs / S-rGO / GCE.

[0062] Using Ni-CNTs / S-rGO / GCE as the working electrode, platinum electrode as the auxiliary electrode, saturated calomel electrode as the reference electrode, and hydrochloric acid solution of capsaicin with a pH of 1 and a concentration of 50μM as the electrolyte, the effects of deposition potential, deposition time, and electrolyte pH on the peak current of capsaicin were investigated. When investigating the deposition potential, the scan rate was 0.1V / s, the equilibrium time was 2s, the deposition time was 60s, and the pH of the electrolyte was 1. The changes in the peak current intensity of capsaicin at different deposition potentials were investigated; when investigating the deposition time, the potential was -0.1V, the scan rate was 0.1V / s, the equilibrium time was 2s, and the pH of the electrolyte was 1. The changes in the peak current intensity of capsaicin at different deposition times were investigated; when investigating the pH of the electrolyte, the potential was -0.1V, the scan rate was 0.1V / s, the equilibrium time was 2s, and the deposition time was 75s. The changes in the peak current intensity of capsaicin at different pH values ​​were investigated. The results are as follows: Fig. 9 As shown, from Fig. 9 It can be seen from a that in the range of -0.4 to -0.1 V, the peak current of capsaicin increases with the increase of deposition potential and reaches the maximum at -0.1 V. In the range of -0.1 to 0.2 V, the peak current of capsaicin decreases with the increase of deposition potential. Therefore, -0.1 V is selected as the optimal deposition potential. Fig. 9 As can be seen from b, when the deposition time increases from 15s to 75s, the peak current increases continuously, but when the deposition time continues to increase from 75s to 180s, the peak current has no obvious increase and remains in a relatively stable range. Therefore, 75s is selected as the optimal deposition time. Fig. 9 c It can be concluded that as the pH gradually increases, the current value decreases significantly, so the optimal deposition pH = 1.

[0063] Example 3

[0064] A method for detecting capsaicin content comprises the following steps:

[0065] 1) Dissolve the capsaicin standard in 0.1M hydrochloric acid aqueous solution to obtain capsaicin-hydrochloric acid aqueous solution with final concentrations of 0, 5μM, 10μM, 20μM, 25μM, 30μM, 50μM, 60μM, 70μM, 80μM, 90μM, and 100μM;

[0066] 2) The electrochemical sensor (Ni-CNTs / S-rGO / GCE) for detecting capsaicin prepared in Example 2 was used as the working electrode, the platinum electrode was used as the auxiliary electrode, and the saturated calomel electrode was used as the reference electrode to form a three-electrode system to detect the above samples. The deposition time of the above samples was 75s. The differential pulse voltammetry test conditions are as follows: the potential range is 0.2-0.9V, the pulse amplitude is 0.05V, the pulse width is 200ms, the pulse period is 400ms, and the equilibrium time is 2s. Each sample was tested more than 3 times and the average value was taken;

[0067] 3) If Fig.10 As shown, the linear regression equation of the response current and capsaicin concentration is as follows: I1 = 0.002 + 0.568C, R1 2 =0.9978 (capsaicin concentration range: 0.01-20.00 μmol / L); I2 = -1.096 + 0.750 2 C, R2 2 =0.999 (capsaicin concentration range: 20.00~100.00μmol / L), I represents the current intensity, in μA, and C represents the capsaicin concentration, in μmol / L. According to the method provided by IUPAC, the LOD of Ni-CNTs / S-rGO / GCE sensor for capsaicin is calculated to be 1nmol / L (S / N=3). This shows that Ni-CNTs and S-rGO can achieve ultra-sensitive detection of capsaicinoids.

[0068] 4) Detection of current value of the sample to be tested: extract capsaicin from duck neck by crushing 3-5 g of duck neck, adding 20 mL of 80% methanol aqueous solution and 0.2 mL of 220 g / L zinc acetate solution, ultrasonicating at 60°C for 30 min, cooling in a -20°C refrigerator for 15 min, filtering, collecting the filtrate, repeating the above operation on the residue and extracting it again, combining the filtrate, and finally fixing the volume to 50 mL with 80% methanol aqueous solution, filtering with a 0.45 μm filter membrane before testing; dissolving 0.05 mL of the filtered test solution in 0.1 M hydrochloric acid aqueous solution, testing its response current under the test conditions in step 2), substituting the measured response current value into the linear regression equation in step 3), and then calculating the capsaicin content.

[0069] Example 4

[0070] Stability test of Ni-CNTs / S-rGO / GCE electrochemical sensor

[0071] (1) A 50 μM capsaicin standard solution (sample) was prepared by dissolving a capsaicin standard in a 0.1 M hydrochloric acid aqueous solution, and an electrochemical sensor (Ni-CNTs / S-rGO / GCE) for detecting capsaicin was prepared using 8 glassy carbon electrodes according to the method in Example 2;

[0072] (2) A three-electrode system consisting of 8 sensors as working electrodes, a platinum electrode as an auxiliary electrode, and a saturated calomel electrode as a reference electrode was used to test the above samples on the 5th, 10th, 15th, 20th, 25th, and 30th days. The differential pulse voltammetry test conditions were as follows: potential range 0.2-0.9V, pulse amplitude 0.05V, pulse width 200ms, pulse period 400ms, and equilibrium time 2s. Each sample was tested more than 3 times and the average value was taken;

[0073] like Fig.11 As shown, from Fig.11 a It can be seen that there is no significant difference in the results of capsaicin detection among the 8 different sensor groups, and the relative standard deviation within the group is less than 4.51%, indicating that different Ni-CNTs / S-rGO / GCE sensors have good inter-group and intra-group stability. The storage stability results of Ni-CNTs / S-rGO / GCE are shown in Fig.11 b, With the extension of storage time, the response current of capsaicin on Ni-CNTs / S-rGO / GCE remained basically unchanged, which indicates that Ni-CNTs / S-rGO / GCE has good storage stability.

[0074] Example 5

[0075] Anti-interference test of Ni-CNTs / S-rGO / GCE electrochemical sensor

[0076] (1) A 50 μM capsaicin standard solution was prepared by dissolving a capsaicin standard in a 0.1 M hydrochloric acid aqueous solution, and cholesterol (final concentration 2.6 μmol / L), glucose (final concentration 500 μmol / L), sucrose (final concentration 500 μmol / L), KCl (final concentration 0.01 mol / L), NaCl (final concentration 0.01 mol / L), CaCl2 (final concentration 0.01 mol / L), MgCl2 (final concentration 0.01 mol / L) and NaNO3 (final concentration 0.01 mol / L) were added to prepare a sample, and the sample was compared with a 0.1 M hydrochloric acid aqueous solution sample containing only a 50 μM capsaicin standard;

[0077] (2) The electrochemical sensor (Ni-CNTs / S-rGO / GCE) for detecting capsaicin prepared in Example 2 was used as the working electrode, the platinum electrode was used as the auxiliary electrode, and the saturated calomel electrode was used as the reference electrode to form a three-electrode system to detect the above samples respectively. The differential pulse voltammetry test conditions were as follows: the potential range was 0.2-0.9V, the pulse amplitude was 0.05V, the pulse width was 200ms, the pulse period was 400ms, and the equilibrium time was 2s. Each sample was tested more than 3 times and the average value was taken;

[0078] Depend on Fig.12 As shown in the figure, there is no significant difference between the peak current of capsaicin and the blank group after adding 2.6μmol / L cholesterol, 500μmol / L glucose, 500μmol / L sucrose and five concentrations of 0.01mol / L KCl, NaCl, CaCl2, MgCl2 and NaNO3, indicating that these substances have little interference with the detection of capsaicin. Therefore, it is concluded that Ni-CNTs / S-rGO / GCE has good anti-interference performance.

[0079] Example 6

[0080] Spike recovery analysis

[0081] (1) Different concentrations (5, 10, and 20 μmol / L) of capsaicin and dihydrocapsaicin standard solutions were added to the leisure duck neck, leisure beef, and leisure chicken feet samples, respectively, and three parallel samples were prepared for each concentration.

[0082] (2) Using the capsaicin extraction method of Example 3, capsaicin extracts from leisure duck neck, leisure beef and leisure chicken feet were obtained respectively;

[0083] (3) According to the detection method of Example 3, the content of capsaicinoids in leisure duck neck, leisure beef and leisure chicken feet was obtained, and the spiked recovery rate was calculated;

[0084] The spiked recoveries of capsaicin and dihydrocapsaicin in the extracts of leisure duck neck, leisure beef and leisure chicken feet were determined by Ni-CNTs / S-rGO / GCE. As shown in Table 1, the recovery of capsaicin is between 92.00 and 113.60%, the recovery of dihydrocapsaicin is between 92.50 and 112.60%, and the recovery of the mixed solution of capsaicin and dihydrocapsaicin in equal proportions is between 96.27 and 115.80%. In addition, the RSDs of capsaicin, dihydrocapsaicin, and the mixed solution of capsaicin and dihydrocapsaicin are less than 5.70%, 6.07%, and 5.69%, respectively. This shows that Ni-CNTs / S-rGO / GCE has feasible practical application potential.

[0085] Table 1 Spiked recovery results of capsaicin and dihydrocapsaicin

[0086]

[0087]

[0088] The detailed description of the electrochemical sensor for capsaicinoids constructed with Ni-enhanced CNTs / sulfonated rGO composite materials in the above reference embodiments is illustrative rather than restrictive, and several embodiments can be listed according to the limited scope. Therefore, changes and modifications without departing from the overall concept of the present invention should fall within the scope of protection of the present invention.

Claims

1. A method for preparing a Ni-enhanced CNTs / sulfonated rGO composite material, characterized in that: The preparation method comprises the following steps: (1) dispersing graphene oxide in ultrapure water, adding 4-HBS thereto and stirring to mix evenly, then transferring to a reactor, hydrothermally reacting at 120-150°C for 4-8h, washing and drying to obtain sulfonated rGO material; (2) Dispersing Ni-enhanced CNTs material and sulfonated rGO material in ultrapure water and subjecting them to ultrasonic reaction to obtain Ni-enhanced CNTs / sulfonated rGO composite materials; In step (1), the mass ratio of graphene oxide to 4-HBS is 15-25:1; In step (2), the mass ratio of Ni-enhanced CNTs material to sulfonated rGO material is 1:1.5-3.

2. The preparation method according to claim 1, characterized in that: In step (2), the ultrasonic reaction time is 1.5 to 3 hours.

3. The Ni-enhanced CNTs / sulfonated rGO composite material prepared by the preparation method according to claim 1 or 2, characterized in that: In the Ni-enhanced CNTs / sulfonated rGO composite material, tubular Ni-enhanced CNTs cover the surface of layered sulfonated rGO, and the sulfonated rGO sheets wrapped by Ni-CNTs are alternately stacked to form a three-dimensional structure.

4. An electrochemical sensor for detecting capsaicinoids, characterized in that: It comprises an electrode and a composite material loaded on the electrode; the composite material is the Ni enhanced CNTs / sulfonated rGO composite material as described in claim 3.

5. The method for preparing an electrochemical sensor for detecting capsaicinoids as claimed in claim 4, characterized in that: An aqueous solution containing Ni-enhanced CNTs / sulfonated rGO composite material is drop-coated on the surface of a clean glassy carbon electrode, and after drying, an electrochemical sensor for detecting capsaicinoids can be obtained.

6. Use of the electrochemical sensor for detecting capsaicinoids as claimed in claim 4 in detecting the content of capsaicinoids.

7. A method for detecting the content of capsaicinoids, characterized in that: The detection method comprises the following steps: 1) Dissolve equal volumes of capsaicin standard solutions or dihydrocapsaicin standard solutions with different concentration gradients in the electrolyte solution; 2) using the electrochemical sensor according to claim 4 as a working electrode, and forming a three-electrode system with an auxiliary electrode and a reference electrode to detect the electrochemical signals of each sample in step 1); 3) With the response value of the electrochemical signal as the ordinate and the concentration of the capsaicin standard solution or the dihydrocapsaicin standard solution as the abscissa, a standard curve is constructed and a linear equation is derived; 4) Extract capsaicin or dihydrocapsaicin from the sample to be tested and dissolve it in an electrolyte solution, repeat the above step 2), substitute the response value of the electrochemical signal obtained into the linear equation obtained in step 3), and the content of capsaicinoids can be calculated.

8. The detection method according to claim 7, characterized in that: The electrolyte solution is a hydrochloric acid aqueous solution; the auxiliary electrode and the reference electrode are a platinum electrode and a saturated calomel electrode respectively.

9. The detection method according to claim 7, characterized in that: In step 2), differential pulse voltammetry or cyclic voltammetry can be used for detection.

Citation Information

Patent Citations

  • Preparation method of three-dimensional structure nano carbon material reinforced nickel-based composite material

    CN111979450A

  • Electrochemical sensor for detecting capsaicin and capsaicin content detection method

    CN112924520A